The Immune Barrier of Porcine Uterine Mucosa Differs Dramatically at Proliferative and Secretory Phases and Could Be Positively Modulated by Colonizing Microbiota - Han, Deping; Sun, Peng; Hu, Yanxin; Wang, Jing; Hua, Guoying; Chen, Jianfei; Shao, Chuyun; Tian, Fan; Darwish, Hesham Y. A.; Tai, Yurong; Yang, Xue; Chang, Jianyu; et al. (Frontiers in Immunology, 2021)
Endometrial immune response is highly associated with the homeostatic balance of uterus and embryo development; however, the underlying molecular regulatory mechanism(s) are not fully elucidated. Herein, the porcine endometrium showed significant variation in mucosal immunity in proliferative and secretory phases by single cell RNA sequencing. The loose arrangement and high motility of uterine epithelium in proliferative phase gave opportunities for epithelial cells and dendritic cells to crosstalk with colonialized microbial community guiding lymphocytes migration into the mucosal and glandular epithelium. The migrating lymphocytes were primarily NK and CD8+ T cells, which were robustly modulated by the chemokine signaling. In the secretory phase, the significantly strengthened mechanical mucosal barrier and increased immunoglobulin A, alleviated the migration of lymphocytes into the epithelium when the neuro-modulation, mineral uptake, and amino acid metabolism were strongly up-regulated. The noticeably increased intraepithelial lymphocytes were positively modulated by the bacteria in the uterine cavity. Our findings illustrated significant mucosal immunity variation in the endometrium in proliferative and secretory phases was closely related to intraepithelial lymphocytes migration, which could be modulated by the colonialized bacteria after cross-talk with epithelial cells with higher expressions of chemokine.